Estimation of Betamethasone in Pharmaceutical Dosage Forms by Visible Spectrophotometry - Ravi Kumar, D.; Vardhan, S.V.M.; Ramachandran, D.; Rambabu, C. (Asian Journal of Chemistry, 2012)
Simple, accurate, precise and reproducible methods have been developed and validated for the estimation of betamethasone in pharmaceutical dosage forms by visible spectrophotometry. Method-A is based on the reduction of molybdate in acidic medium by betamethasone, producing one or two more of the possible reduced species which have a characteristic intense blue colour (molybdenum blue) chromogen exhibiting lmax at 670 nm. Method-B is based on the oxidation of a-ketol portion of betamethasone to formaldehyde and then converted into its phenyl hyrdazone and then a red colour is developed under the action of oxidizing agent [hexacyano ferrate(III)] in acid medium exhibiting lmax at 520 nm. The results of analysis have been validated statistically and recovery studies confirm the accuracy of the proposed methods. The methods proposed are applied to various pharmaceutical dosage forms as well.